Pelatihan Model Pembelajaran Project-based Learning bagi Guru Sekolah Dasar Negeri 3 Karanganom Klaten - Putri Zudhah Ferryka; Sri Suwartini; Isna Rahmawati; Nela Rofisian (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2023)
Community service in project-based learning model training aims to introduce learning models that can be applied in elementary schools. The project-based learning model can be applied to all subjects in elementary schools. In this way, learning activities become higher quality, more interesting for students, less boring, meaningful, and innovative. The service participants consisted of the principal, all teachers, and all students carrying out field learning practices at SD N 3 Karanganom Klaten. The method used in this training is participatory action research (PAR), which consists of demonstration activities, mentoring, and discussions. Five materials are provided in this training, namely understanding, objectives, syntax, and application in learning and assessment systems. The results of this service activity show the training participants' success in mastering the five pieces of material. This can be seen from the high enthusiasm in every stage of the training implementation.